2017
DOI: 10.1371/journal.pone.0186100
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones and psychological responses to soccer matches: Insights from a systematic review and meta-analysis

Abstract: The present systematic review and meta-analysis aimed to assess the perturbations in hormonal and psychological homeostasis in response to soccer match-play. These perturbations were explored according to match outcome (i.e., win versus loss), gender, type of contest (i.e., competitive versus non-competitive fixtures) and competitive level (i.e., novice versus high-level). The review was conducted according to the Population/Intervention or Exposure/Comparison/Outcome(s) (PICO) criteria and the Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
(55 reference statements)
0
29
1
1
Order By: Relevance
“…Therefore, the greater chronological age, hence greater training experience of soccer players in the study of Penailillo et al (2015) , could have induced a reduced hormone response during a competitive match compared to the less experienced U17 soccer players recruited in our study. In addition, several other factors have been identified to play a role in the hormone response to a soccer match ( Kobayashi and Miyazaki, 2015 ; Slimani et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the greater chronological age, hence greater training experience of soccer players in the study of Penailillo et al (2015) , could have induced a reduced hormone response during a competitive match compared to the less experienced U17 soccer players recruited in our study. In addition, several other factors have been identified to play a role in the hormone response to a soccer match ( Kobayashi and Miyazaki, 2015 ; Slimani et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal response to a soccer match is a hot topic, with anabolic (i.e., testosterone [T]) and catabolic (i.e., cortisol [C]) hormones potentially influencing the performance and health status of the athlete ( Slimani et al, 2017 ). At the same time, their ratio testosterone:cortisol (T:C) is considered a physiological stress indicator associated to overtraining ( Hayes et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hormonal stress response is modulated by different contextual factors that would induce different responses depending on the psychological interpretation of the subject of the environment. Factors as motivation, the seriousness of the competition and competition level are main parameters that would modulate the hormonal stress response, being these parameters, poor join studied [17].…”
Section: Introductionmentioning
confidence: 99%
“…The type sport and competition, competition season periodization, and intensity of exercise, along with considering gender and age, can increase the generalizability of future studies. In this regard, recent reviews and observational experiences ( Ehrlenspiel and Strahler, 2012 ; Slimani et al, 2017 ; van Paridon et al, 2017 ) have indicated that some variables are associated with the psychophysiological changes to competition in elite athletes (e.g., challenge of transfer to the new team and club, location of competition, habituation to stressful competitions, poor sleep, referee and rivals, gender, type of sport, social interaction with fans, media and organizations, warm-up and preparing for competition, coaching styles, social support, expectations, preparation levels, success and failure profiles, commitments and plans, etc.). Each of these variables is worth investigating in the field of telomere biology in future studies.…”
Section: Discussionmentioning
confidence: 99%